Memorial dedicated to James Fawcett Esq. - Ghosh, Ayan (2023)
Memorial dedicated to James Fawcett Esq. and his two infant children, erected by his widow upon his death on 17th September 1831 at London, aged 31 years. His mother, Helen Hitchens, was the daughter of Major General John Bellasis, an East India Company officer and commander of the forces at Mumbai. James Fawcett had, for a period, lived with his family at Mumbai, where he was partner in the firm Messrs. Remington & Co.